Problemy zarządzania zasobami ludzkimi w Chińskiej Republice Ludowej - Selinger, Natalia (Problems of Human Resources Management in China, 2008)
In the article, the author makes an attempt to identify human resources management (HRM) in China given the current determinants. In addition, the author indicates key challenges facing HRM in China. Throughout the article strong references are made to state-owned enterprises and public sector organizations.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 213-222